PaO2/FiO2 Ratio as Predictor of Mortality in Neonates with Meconium Aspiration Syndrome - Narayanan, Anand; Batra, Prerna; Faridi, Mohammed Mounis Akbar; Harit, Deepika (American Journal of Perinatology, 2019)
Objectives Partial arterial pressure of oxygen/fraction of oxygen in inspired air (PaO2/FiO2) ratio has been used as a predictor of outcome in some neonatal conditions, but has not been used in meconium aspiration syndrome (MAS). This study was conducted with the objective to study if the PaO2/FiO2 ratio of < 200 at 6, 12, and 24 hours of life can predict mortality in neonates with MAS.Study Design Two hundred neonates with MAS were included in the study. PaO2/FiO2 ratio was calculated at 6, 12, and 24 hours of life. Sensitivity, specificity, predictive values, and likelihood ratio at cut-off < 200 to predict mortality was calculated.Results PaO2/FiO2 ratio at cut-off of < 200 was found to predict mortality in neonates with MAS with 94.1% sensitivity and 96.6% specificity. It was also able to predict development of severe MAS.Conclusion PaO2/FiO2 at < 200 can predict all-cause mortality in neonates with MAS. It can be used as vital tool in identifying newborns at high risk, thus helping in focused care.
Keywords: PaO2/FiO2 ratio; MAS; neonates